ANALISIS DEFORESTASI DI DAERAH ALIRAN SUNGAI (DAS) KRUENG PEUSANGAN TAHUN 2022-2023: Analysis of Deforestation in the Krueng Peusangan River Basin From 2022-2023 - nuraida, nuraida; Hafaz Furqan; Sayed Ahmad Zaki Yamani (Jurnal Lingkungan Almuslim, 2024)
River Watersheds (DAS) in Indonesia have an important role in the hydrological cycle and ecosystem, but many are in critical condition due to high deforestation. This research focuses on the Peusangan watershed in Aceh Province, which has experienced significant levels of deforestation in recent years. The aim of the research is to analyze the rate of deforestation in the Peusangan watershed in 2022-2023 and understand its impact on the local ecosystem. The method used involves analyzing land cover data using Geographic Information System (GIS) technology with satellite image data. The research results show that there was forest loss of 1,066 hectares during this period, with a deforestation percentage of 1.49%. These findings provide a real picture of the forest damage that has occurred and the importance of conservation measures to maintain the sustainability of the Peusangan watershed ecosystem. It is also hoped that this information can increase public awareness about the negative impacts of deforestation and encourage active participation in forest conservation efforts.